Hubungan Kelekatan Orangtua-Remaja dengan Kemandirian pada Remaja di Smkn 1 Denpasar - Dewi, Audy Ayu Arisha; Valentina, Tience Debora (Jurnal Psikologi Udayana, 2013)
In adolescence, there are several developmental tasks that must be faced, one of which is the development of autonomy. Role of parents can’t be separated on the formation of adolescent autonomy because of an emotional connection between parents and adolescence. Emotional connection that persists for long periods is called attachment. This study aimed to determine the relationship between parent-adolescent attachment with adolescent autonomy in SMKN 1 Denpasar.   The sampling technique used in this study is simple random sampling. Subjects of this research are 330 students in SMKN 1 Denpasar, from age 15-18 years old. Researcher deploy two scales, the parent-adolescent attachment scale adapted from the Inventory Parent and Peer Attachment (Armsden & Greenberg, 1987) and autonomy scale is based on aspects that proposed by Steinberg (2009). The data obtained in this study were analyzed by simple regression analysis to examine the relationship between parent-adolescent attachment and autonomy.   Regression analysis results t value 3,652 and P = 0.000 (P < 0.05). It means attachment to parents and adolescent autonomy are significantly and positively correlated, when parent-adolescent’s attachment is high they will have a high score on autonomy too. Coefficient of determination equal to 0.039 indicates the attachment contribution to the autonomy is 3,9%, and  96,1% was contributed by other factors such as gender, birth order, school activities and community activities.   Keywords: attachment, autonomy, adolescence.